This day in network radio a daily calendar of births, deaths, debuts, cancellations and other events in broadcasting history - Cox, Jim 1939- (McFarland, 2008)
"This volume offers a chronological overview of major events, decisions, personalities, and broadcast features that have significantly affected American network radio since its inception in the mid-1920s"--Provided by publisher